Mesenchymal tumours of the mediastinum—part I - den Bakker, Michael A. (Virchows Arch, 2015)
The mediastinum is an anatomically defined space in which organs and major blood vessels reside with surrounding soft tissue elements. The thymus is an important organ in the mediastinum, and many of the masses encountered in the mediastinum are related to this organ. Most neoplasms diagnosed in the mediastinum are epithelial tumours (thymomas and thymic carcinomas), lymphomas or germ cell tumours. In contrast, soft tissue tumours of the mediastinum are rare. In 1963, Pachter and Lattes systematically reviewed soft tissue pathology of the mediastinum, covering the hitherto described [2, 226, 227] In this review, based on the 2013 WHO classification of soft tissue tumours and the 2015 WHO classification of tumours of the lung, pleura, thymus and heart, we provide an updated overview of mesenchymal tumours that may be encountered in the mediastinum.